IMPLEMENTASI UNDANG-UNDANG NO 22 TAHUN 2009 PASAL 291 TENTANG PENGGUNAAN HELM STANDAR NASIONAL INDONESIA DI KOTA PONTIANAK - Yudo Iryanto E.01106120 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article is backgrounded in order to know the lack of society’s attention in using helmet with Indonesian National Standard (SNI), there is no basic standard which is determined by BSN about the detail of SNI helmet which is circulating in Pontianak. The formulation of this research is “ Why the implementation of SNI helmet policy have not maximal”. The aims of this research is to find out and explain about the process of the implementation of the use of SNI helmet policy and factor inhibited factors in the implementation. In this research method, the writer used descriptive research design and technique of collecting data which was used are observation technique, interview, and documentation, meanwhile in  technique of analysis data itself, the writer used descriptive qualitative technique where the data which had collected processing and analysed as qualitative.Based on the data analysis, shows that the process of the implementation of SNI helmet policy can be conclude as follow : basically, socialization of this policy in Pontianak city had been done by the police through some media such as, print media, electronic either to the motorcycle rider on the road by the traffic police directly. On the phase of enforcement/action, the police official only give the warning and direction to the motorcycle rider who careless to use SNI helmet. This is caused by the implementation of use of SNI helmet still in the socialization phase, as a result there is no raid by the police to discipline the use of SNI helmet spesifically. Keywords: The realization and inhibited factor in implementation SNI helmet policy.